Pengembangan Modul Matematika Bernuansa Islam dan Lingkungan pada Materi Bilangan Bulat - Elsa Tia Ariski; Rizki Wahyu Yunian Putra; Arini Alhaq (Journal on Education, 2023)
The development research was conducted as an innovation of learning modules with Islamic nuances and the environment of whole number material at the junior high school / MTs level that are feasible, interesting, and effective for use in learning. The development model used is the ADDIE model. The data analysis technique used is the analysis of validation of material, media, and religious experts, the response of the attractiveness of educators and students, and the effectiveness test. The feasibility test was conducted by three material expert validators, three media experts, and one religious expert. Attractiveness and effectiveness response tests were conducted at SMP Swadiri 1 Seputih Agung and MTs Darussalam Adijaya. The results of the feasibility test by material expert validators 3.53, media experts 3.69, and religious experts 3.77 with the criteria "feasible". The attractiveness response test by educator 1 was 3.88 and educator 2 was 3.29 with the criteria "very interesting", the response of students in the small group test was 3.53, the large group was 3.57 with the criteria "very interesting" at SMP Mandiri 1 Seputih Agung and the small group 3.57 and the large group 3.60 with the criteria of "very interesting" at MTs Darussalam Adijaya. The product effectiveness results obtained an effect size score of 0.68 in the "medium" category at SMP Swadiri 1 and 0.85 in the "high" category at MTs Darussalam Adijaya so that the module was declared effective for use in learning. Therefore, it can be concluded that the mathematics module with Islamic nuances and the material environment for integers is feasible, interesting, and quite effective in learning.